Gadamerian Hermeneutical Analysis of Hasbi Ash-Shiddieqy's Interpretation of QS. Luqman (31):6 in the Context of Contemporary Entertainment Discourse - Fitra, Akhmad Aidil; Aboujanah, Yousuf (Universitas Islam Tribakti Lirboyo Kediri, 2025)
One of the challenges faced by contemporary Muslims is the relevance of classical Qur'anic interpretation in addressing modern issues. This study examines Hasbi Ash-Shiddieqy's interpretation of QS. Luqman (31):6 through the lens of Gadamerian hermeneutics, particularly in the context of contemporary entertainment discourse. The verse, often associated with prohibitions on futile speech and entertainment, has been widely debated in Islamic scholarship. This research employs a text-based qualitative method, utilizing Gadamer's philosophical hermeneutics-especially the concepts of the